Abuse Potential of Oral Phendimetrazine in Cocaine-dependent Individuals: Implications for Agonist-like Replacement Therapy. Issue 3 (May 2016) - Bolin, B. Levi; Stoops, William W.; Sites, Jeremy P.; Rush, Craig R.
Abstract : Objectives: Phendimetrazine is a prodrug for the monoamine releaser phenmetrazine—a drug with known abuse potential. Preclinical studies suggest that phendimetrazine has limited abuse potential and may have promise as an agonist-like replacement therapy for cocaine dependence. This study evaluated the abuse potential of phendimetrazine in humans. Methods: Nine cocaine-dependent individuals (N = 9) were enrolled to investigate the abuse potential of phendimetrazine and d-amphetamine, using a double-blind, placebo-controlled, within-subject design. Subjective and cardiovascular effects of oral phendimetrazine (35, 70, and 105 mg), d-amphetamine (10, 20, and 30 mg), and placebo were assessed in quasi-random order across 8 sessions lasting for approximately 8 hours each. Results: d-Amphetamine (20 and 30 mg) significantly increased cardiovascular measures in a time and dose-related manner, but phendimetrazine did not systematically alter cardiovascular measures. Although d-amphetamine and phendimetrazine significantly increased ratings indicative of abuse potential (eg, drug liking) and stimulant-like effects relative to placebo, these increases were generally small in magnitude, with phendimetrazine producing significant effects on fewer abuse-related measures and at fewer time points than d-amphetamine. Conclusions: These preliminary findings suggest that oral phendimetrazine and d-amphetamine may have limited abuse potential in cocaine-dependent individuals. These findings collectively emphasize that the clinical utility of medications to treat cocaine-use disorders should be weighed carefully against their potential for abuse and diversion, with careful attention paid to evaluating abuse potential in a clinically relevant population of interest. Future studies are needed to further elucidate the potential utility of phendimetrazine as an agonist-like replacement therapy for cocaine dependence.